Dip-coating of MXene and transition metal dichalcogenides on 3D-printed nanocarbon electrodes for the hydrogen evolution reaction - Kandambath Padinjareveetil, Akshay Kumar; Ghosh, Kalyan; Alduhaish, Osamah; Pumera, Martin (Elsevier, 2021)
3D-printing technology is widely accepted as a scalable and advanced manufacturing procedure for the fabrication of electrodes for electrochemical applications. 3D-printed carbon-based electrodes can be used for electrochemical analysis, replacing conventional carbon electrodes. However, a bare 3D-printed carbon electrode exhibits poor electrochemical performance. Herein, a post-treatment of 3D-printed electrodes was carried out using catalytically active materials to improve their electrochemical performance. We used a dip-coating technique which is a more universal, facile, and cost-effective approach compared with other conventionally used techniques such as atomic layer deposition or electrodeposition. The 3D-printed nanocarbon electrodes were dipcoated with MXene (Ti3C2Tx) and different transition metal dichalcogenides such as MoS2, MoSe2, WS2, and WSe2 to study their catalytic activity towards the hydrogen evolution reaction (HER). This study demonstrates a simple method of improving the catalytic surface properties of 3D-printed nanocarbon electrodes for energy conversion applications.

3D-printing technology is widely accepted as a scalable and advanced manufacturing procedure for the fabrication of electrodes for electrochemical applications. 3D-printed carbon-based electrodes can be used for electrochemical analysis, replacing conventional carbon electrodes. However, a bare 3D-printed carbon electrode exhibits poor electrochemical performance. Herein, a post-treatment of 3D-printed electrodes was carried out using catalytically active materials to improve their electrochemical performance. We used a dip-coating technique which is a more universal, facile, and cost-effective approach compared with other conventionally used techniques such as atomic layer deposition or electrodeposition. The 3D-printed nanocarbon electrodes were dipcoated with MXene (Ti3C2Tx) and different transition metal dichalcogenides such as MoS2, MoSe2, WS2, and WSe2 to study their catalytic activity towards the hydrogen evolution reaction (HER). This study demonstrates a simple method of improving the catalytic surface properties of 3D-printed nanocarbon electrodes for energy conversion applications.
Dip-coating of MXene and transition metal dichalcogenides on 3D-printed nanocarbon electrodes for the hydrogen evolution reaction
Keywords: Fused deposition modeling; Dip-coating; MXene; TMDs; Hydrogen evolution reaction; Fused deposition modeling; Dip-coating; MXene; TMDs; Hydrogen evolution reaction